Peningkatan Kemampuan Guru Melaksanakan Percobaan IPA Sederhana dalam Pembelajaran IPA SD - Andi Makkasau; Patta Bundu (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
This classroom action research was designed to improve the capabilities of primary school teachers' in applying simple experimenta-tions in science learning. This three cycles study was held in class III of a public primary school in Makassar Muicipality. Data were collected by observation, interviews, and discussion, and then analyzed by percentage in the end of each cycle. The results indicated that the teachers' capabilities seemed to be increased in planning experimentations, in designing work-sheets, and in guiding pupils' practices.